Cyclosporine in Pediatric Nephrology (Iranian Journal of Kidney Diseases, 2018)
Cyclosporine began to be used as one of the immunosuppressive agents in transplantation in the beginning of the 1980s, and in the treatment of nephrotic syndrome in the pediatric nephrology. Therapeutic area of cyclosporine is narrow and its side effects limit its usage. Preference for cyclosporine and tacrolimus as a calcineurin inhibitor is left for the choice of the department. There are still countries with preferred-cyclosporine use because of economic reasons. Cyclosporine is currently being used in the treatment of nephrotic syndrome, but due to its high relapse rates in a short-term use, and nephrotoxicity in long-term use, search for new drugs with fewer side effects keeps continuing. As long as its use is indispensable, it will be necessary to keep track of kidney function and blood level of this medication closely to protect the patients from toxicity.